Fabric, form, function: anomalous tempers in fineware ceramics from El-Mahasna, Egypt - Peasley, Dustin J. (My University, 2010)
During the 1995-2000 seasons of the el-Mahasna Archaeological Project in Egypt, a small proportion of the recovered fineware sherd assemblage was identified as having been manufactured using anomalous tempers relative to the majority of those recovered. This paper will discuss the results of an analysis of these ceramics conducted during the recent 2009/2010 excavation season. In particular, this study examined the relationship between fabric, form, and function within the fineware ceramics at el-Mahasna in an attempt to determine if temper was related to vessel function or rather was the result of the region of origin of the vessels.
Keywords: Egypt -- Antiquities.; El Mahasna Site (Egypt); Excavations (Archaeology) -- Egypt.; Archaeology and history.; Archaeology -- Methodology.